Wavelength-Dependent Photochemistry and Biological Relevance of a Bilirubin Dipyrrinone Subunit - Madea, Dominik; Mahvidi, Sadegh; Chalupa, David; Mujawar, Taufiqueahmed; Dvořák, Aleš; Muchová, Lucie; Janoš, Jiří; Slavíček, Petr; Švenda, Jakub; Vítek, Libor; Klán, Petr (The Journal of organic chemistry, 2020)
Phototherapy is a standard treatment for severe neonatal jaundice to remove toxic bilirubin from the blood. Here, the wavelength-dependent photochemistry of vinylneoxanthobilirubic acid methyl ester, a simplified model of a bilirubin dipyrrinone subunit responsible for a lumirubin-like structural rearrangement, was thoroughly investigated by liquid chromatography and mass and absorption spectroscopies, with the application of a multivariate curve resolution analysis method supplemented with quantum chemical calculations. Irradiation of the model chromophore leads to reversible Z → E photoisomerization followed by reversible photocyclization to a seven-membered ring system (formed as a mixture of diastereomers). Both the isomerization processes are efficient (ΦZE ∼ ΦEZ ∼ 0.16) when irradiated in the wavelength range of 360-410 nm, whereas the E-isomer cyclization (Φc = 0.006-0.008) and cycloreversion (Φ-c = 0.002-0.004) reactions are significantly less efficient. The quantum yields of all processes were found to depend strongly on the wavelength of irradiation, especially when lower energy photons were used. Upon irradiation in the tail of the absorption bands (490 nm), both the isomers exhibit more efficient photoisomerization (ΦZE ∼ ΦEZ ∼ 0.30) and cyclization (Φc = ∼0.07). In addition, the isomeric bilirubin dipyrrinone subunits were found to possess important antioxidant activities while being substantially less toxic than bilirubin.
Keywords: Phototherapy; novorozenecká žloutenka; Infant, Newborn; bilirubin; Bilirubin; novorozenec; Humans; isomerie; Photochemistry; fotochemie; Isomerism; fototerapie; Jaundice, Neonatal; lidé